A Study on the Dynamic Responses and Joints Clearance Optimization of the Planar Operating Mechanism of High-Voltage Circuit Breaker. (2nd May 2019) - Li, Xiaofeng; Wu, Shijing; Li, Xiaoyong; Zhao, Deng; Li, Qiaoquan
Abstract : The operating mechanism is responsible for a large part of machinery faults of high-voltage circuit breaker, which plays a crucial role in the reliability of the power grid. It consists of multiple flexible links connected by revolute joints with inevitable clearances between adjacent links. Flexible links and joints clearance have negative effects on the performance of the whole mechanical system. In this study, the dynamic simulation model of the multiple links articulated operating mechanism is built, and its validity is testified by operation experiment. Then, numerical simulation investigations are implemented to analyze the effects of flexible links and joints clearance on the dynamic responses of the operating mechanism. The results demonstrate that both flexible links and joints clearance exert associated negative effects on the mechanism performance. Furthermore, aimed at improving the dynamic characteristics of the operating mechanism, the joints clearance sizes are selected as design variables, and correlated optimization works are performed. After that, the acceleration and reaction force curves of the mechanical system become smoother, and the amplitudes of the two curves are reduced distinctly.